2009
DOI: 10.1016/j.jog.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and magnetic data inversion for 3D topography of the Moho discontinuity in the northern Red Sea area, Egypt

Abstract: Please cite this article as: Prutkin, I., Saleh, A., Gravity and magnetic data inversion for 3D topography of the Moho discontinuity in the northern Red Sea area, Egypt, Journal of Geodynamics (2008Geodynamics ( ), doi:10.1016Geodynamics ( /j.jog.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…These models stimulated new studies of the crustal structure, particularly the determination of the Moho boundary in Egypt and surrounding areas (e.g., Azab et al, 2015;Cowie and Kusznir, 2012;Prutkin and Saleh, 2009;Salem et al, 2013;Sobh et al, 2016). The results obtained in these studies are very controversial.…”
Section: Introductionmentioning
confidence: 99%
“…These models stimulated new studies of the crustal structure, particularly the determination of the Moho boundary in Egypt and surrounding areas (e.g., Azab et al, 2015;Cowie and Kusznir, 2012;Prutkin and Saleh, 2009;Salem et al, 2013;Sobh et al, 2016). The results obtained in these studies are very controversial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied in global studies when inverting gravity or magnetic data in terms of major interface surfaces in planetary bodies (Prutkin 1989(Prutkin , 2008. In regional studies it has been applied to invert gravity and magnetic data in order to determine the Moho boundary in the Red Sea area (Prutkin & Saleh 2009). The capabilities of the method for interpreting gravity data in local/regional structural studies were demonstrated also on the Kolárovo gravity high (Prutkin et al 2011).…”
Section: Inversion Methodsmentioning
confidence: 99%
“…The density contrast and the vertical position -depth D of the horizontal asymptotic plane -are pre-specified. The mathematical apparatus for this inversion procedure is described in detail in (Prutkin & Saleh 2009). The solution of our non-linear inversion can also consist of a combination of anomalous bodies and contact surfaces.…”
Section: Inversion By the Methods Of Local Correctionsmentioning
confidence: 99%
“…An unknown 3D topography is determined by the equation z = z(x, y). We find an unknown function z(x, y) from the corresponding nonlinear integral equation of the 1st kind (Prutkin and Saleh, 2009). We can use gravity or magnetic data directly on the physical surface, approximation with 3D line segments is necessary only if we need to separate sources and estimate their depths.…”
Section: Inversion Algorithmsmentioning
confidence: 99%